Słownictwo emocjonalno-wartościujące jako wynik derywacji semantycznej - Nikołajewa, Tatiana (Studia Rossica Posnaniensia, 2010)
In the article the system character of semantic transformation is proved on the material of emotional-estimated lexicon. The author confirms the position of Kazan linguistic school – a new meaning presumes a new self-functioning word. The investigator offers a scheme of interpretation of semantic derivatives in a specialized dictionary.